Development of polymerase chain reaction (PCR) technique for detection of Mycoplasma hyopneumoniae and Pseudorabies virus in porcine clinical samples - Tan, Shin-Yi (2016)
With recent advancement in molecular biology, molecular detection has become an alternative diagnostic technique. As Aujeszky’s disease and Enzootic Pneumonia caused great economic losses in swine livestock industry, this study aimed to determine suitable primers sets for Pseudorabies virus (PRV) and Mycoplasma hyopneumoniae (Mhyo) detection in clinical samples using PCR. 15 pigs aged approximately 3 months old showing clinical signs of respiratory distress were sampled. Commercial vaccine and positive clinical samples were used as positive control. Each lung and tonsil tissue samples were subjected to conventional PCR assay using 3 different sets of primers designed to target conserved regions of genomic DNA for Mhyo and PRV respectively. Based on PCR assay for lung tissue samples, 3 out of 15 pigs were positive for Mhyo with all 3 primers sets whereas for tonsil tissue samples, all 15 pigs were negative for PRV. To further optimize the current protocol, more sample size and gradient PCR assay should be performed. In conclusion, all the primers sets chosen were suitable to be used for Mhyo and PRV detection using PCR.